Discovery of Natural Separation of Isotopes in Layered Intrusions Provided by the Gradients of a Temperature, of a Pressure and of a Deformation, using Lukkulaisvaara Intrusion (North Karelia) as an Example - Zilbershtein, A. Kh.; Chaihorsky, A. A.; Semenov, V. S. (Innovations in Science and Technology Vol. 7, 2022)
The spatial local anomalies of the concentration ratios for isotopes 143Nd/144Nd (or eNd) and 87Sr/86Sr in Lukkulaisvaara intrusion (North Karelia) were discovered. The physical mechanisms and the descriptions of the effect of an arising of the anomalies were developed and presented. The base of the proposed mechanisms is the phenomena of the migration (diffusion) of components, due to the (T, P (or D)) gradients. The description of the processes of an arising of the gradients of a temperature (T), of a pressure (P) and of a deformation (D) in the layered inhomogeneous intrusion during its formation and evolution, were obtained. It was shown that the gradients can induce the spatial redistribution of the chemical elements and their isotopes in the intrusion. The redistribution, in turn, can lead to the observed spatial concentration anomalies for these components , i.e to the separation of isotopes, in part. There were first obtained the expressions for the diffusion additions to the isotope´s parameter \(ξ\) (\(ξ\)Nd, in part). Greatest study objective was the discovery of separation of isotopes in natural conditions.